2004
DOI: 10.1177/104063870401600601
|View full text |Cite
|
Sign up to set email alerts
|

Biology of PrPsc Accumulation in Two Natural Scrapie-Infected Sheep Flocks

Abstract: Abstract. Sheep scrapie is a prion disease that requires interaction of exogenous prions with host prion protein (PrP) supporting prion formation. Disease is associated with deposition of a host-generated conformational variant of PrP, PrP sc , in a variety of tissues, including brain, resulting in fatal spongiform encephalopathy. Efficiency of PrP sc formation is determined by polymorphisms in the PrP-coding sequence. This article adds to previous data of natural sheep scrapie, concentrating on the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…In this work we confirm, as previously described in other sheep breeds carrying V (Andréoletti et al, 2002) or A (Tuo et al, 2002) at codon 136, that the placentas of fetus with the Q171R dimorphism do not accumulate PrP Sc (Tuo et al, 2002;Andréoletti et al, 2002;Caplazi et al, 2004;Ersdal et al, 2005;Alverson et al, 2006;Lacroux et al, 2007). Furthermore, for the first time, we have extended these results to demonstrate that besides the Q171R dimorphism, N176K is also associated with the lack of accumulation of PrP Sc in the placenta of scrapie-affected ARQ/ARQ sheep, since six ARQN 176 /ARQK 176 fetuses derived from six ARQ/ ARQ wild type sheep did not display PrP Sc accumulation in the placentas (Table 1).…”
Section: Ihc Analysis Showed That Prpsupporting
confidence: 90%
“…In this work we confirm, as previously described in other sheep breeds carrying V (Andréoletti et al, 2002) or A (Tuo et al, 2002) at codon 136, that the placentas of fetus with the Q171R dimorphism do not accumulate PrP Sc (Tuo et al, 2002;Andréoletti et al, 2002;Caplazi et al, 2004;Ersdal et al, 2005;Alverson et al, 2006;Lacroux et al, 2007). Furthermore, for the first time, we have extended these results to demonstrate that besides the Q171R dimorphism, N176K is also associated with the lack of accumulation of PrP Sc in the placenta of scrapie-affected ARQ/ARQ sheep, since six ARQN 176 /ARQK 176 fetuses derived from six ARQ/ ARQ wild type sheep did not display PrP Sc accumulation in the placentas (Table 1).…”
Section: Ihc Analysis Showed That Prpsupporting
confidence: 90%
“…75,[77][78][79][80] Andréoletti and coworkers quantified the levels of PrP Sc found within the placental cotyledon and determined that these tissues contained very high levels of prion: just 47 times less than in the obex. 75 Interestingly, the accumulation of PrP Sc within placental tissues appears to be dictated by the PRNP genotype of both the ewe and fetus as well as the stage of disease progression within the ewe.…”
Section: Environmental Sources Of Prionsmentioning
confidence: 99%
“…75 Where placental accumulation of PrP Sc occurs, it has been shown that this can be with ewes in the clinical and preclinical stages of disease. 75,77,80 It therefore appears that in ovine scrapie the placenta harbors very high levels of prion but in utero transmission is not occurring. However, following parturition placental tissue is a likely source of infective agent in the transmission of disease from ewes to lambs.…”
Section: Environmental Sources Of Prionsmentioning
confidence: 99%
“…Similar findings have been described in studies of the pathogenesis in sheep and mule deer. 1,4,[8][9][10][11]18,19 Prospective studies on captive and free-ranging elk using this technique are in progress. These studies will delineate the diagnostic sensitivity and specificity of RAMALT screening as a method for identification of infected elk herds as part of an integrated management program to reduce the incidence of CWD in Rocky Mountain elk.…”
Section: 4mentioning
confidence: 99%